PENERAPAN HYPNOTEACHING UNTUK MENINGKATKAN KEMAMPUAN SELF-REGULATED LEARNING MAHASISWA PAPUA DALAM MATA KULIAH DESAIN PEMBELAJARAN - Ega Edistria; Bobbi Rahman; Abdul Azis Abdillah (Politeknik Negeri Jakarta, 2019)
AbstractThe low ability of Self-Regulated Learning students who mostly come from the remote area in Papua, motivates researchers to conduct research by applying Hypnoteaching in the learning process. One of the reasons for the low ability of Self-Regulated Learning students is the habit of those who have not been able to regulate and direct themselves in learning. Hypnoteaching, also called giving positive suggestions, is expected to be able to direct their minds to change learning behavior to be organized and directed. In other words, this will affect the ability of student Self-Regulated Learning. The purpose of this study was to find out: 1) how to increase the ability of Papuan Self-Regulated Learning after Hypnoteaching was applied in Mathematics Courses, 2) how students respond to the application of Hypnoteaching in Mathematics Courses. This type of research is Classroom Action Research with the subject of research are Papuan students in the Mathematics Learning Design Course at STKIP Surya Tangerang 2017/2018 Academic Year. Data collection techniques in the form of questionnaires, field notes, and observation sheets. The data analyzed is only questionnaire data by processing questionnaire scores that are converted into interval data, then determined attitude scores and neutral scores. The results showed that the application of hypnoteaching can improve the ability of self-regulated learning for Papuan students to be better. This can be seen from the percentage of attitude scores related to the ability of self-regulated learning which experienced an increase of initially by 61% in the pre-cycle, increasing to 72% in the first cycle and 74% in the second cycle. Regarding student responses, it was concluded that students gave a positive response to the application of hypnoteaching.Key words: Self-Regulated Learning, Hypnoteaching, Classroom Action ResearchAbstrakRendahnya kemampuan Self-Regulated Learning mahasiswa yang mayoritas berasal dari daerah Pedalaman Papua, melatarbelakangi peneliti untuk melakukan penelitian dengan menerapkan Hypnoteaching dalam proses pembelajaran. Salah satu penyebab rendahnya rendahnya kemampuan Self-Regulated Learning mahasiswa adalah kebiasaan mereka yang belum bisa mengatur dan mengarahkan diri sendiri dalam belajar. Hypnoteaching yang disebut juga pemberian sugesti positif diharapkan mampu mengarahkan pikiran mereka untuk merubah perilaku belajar menjadi teratur dan terarah. Dengan kata lain hal tersebut, akan berpengaruh terhadap kemampuan Self-Regulated Learning mahasiswa. Tujuan penelitian ini adalah untuk mengetahui: 1) bagaimanakah peningkatan kemampuan Self-Regulated Learning Mahasiswa Papua setelah diterapkan Hypnoteaching dalam Mata Kuliah Desain Pembelajaran Matematika, 2) bagaimanakah respon mahasiswa terhadap penerapan Hypnoteaching dalam Mata Kuliah Desain Pembelajaran Matematika. Jenis penelitian merupakan Penelitian Tindakan Kelas dengan subjek penelitian adalah mahasiswa Papua pada Mata Kuliah Desain Pembelajaran Matematika di STKIP Surya Tangerang Tahun Pelajaran 2017/2018. Teknik pengumpulan data berupa angket, catatan lapangan, dan lembar observasi. Data yang dianalis hanya data angket dengan cara mengolah skor angket yang dikonversi menjadi data interval, kemudian ditentukan skor sikap dan skor netralnya. Hasil penelitian menunjukan bahwa penerapan hypnoteaching dapat meningkatkan kemampuan self-regulated learning mahasiswa Papua menjadi lebih baik. Hal ini dapat dilihat dari persentase skor sikap terkait kemampuan self-regulated learning yang mengalami peningkatan dari awalnya sebesar 61% pada pra siklus, meningkat menjadi 72% pada siklus I dan 74 % pada siklus II. Terkait respon mahasiswa diperoleh kesimpulan bahwa mahasiswa memberikan respon positif terhadap penerapan hypnoteaching yang dilakukan.Kata kunci: Self-Regulated Learning, Hypnoteaching, Penelitian Tindakan Kelas